The use of hybrid turbine ventilator (HT'l) for effective temperature reduction in different air volume dimension of building. - Abdul Rahman, Abdul Malek (Universiti Sains Malaysia, 2015)
The hybrid solar wind driven turbine venrtilator (HTV) acts as a catalyst and a free-energy stack ventilation strategy by accelerating the extraction of hot air out of building interiors. From literature reviews on the topics related to stack ventilation, fan assisted stack ventilation can maximize both wind an solar energy for rotation that will induce ample air movement required for physiological cooling and hence improving the thermal indoor environment. Main aim of this research is to explore where this HTV canbe used effectively in the overall building envelope, for example, on top of the roof ridege to cool the attic and/or as a chimney alongside the external wall running up vertically from ground to roof level functioning like a 'fireplace' but instead generating air movement indoors and extracting hot air out through the chimney flue.